5(y+6)=y+3+2y

Simple and best practice solution for 5(y+6)=y+3+2y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(y+6)=y+3+2y equation:


Simplifying
5(y + 6) = y + 3 + 2y

Reorder the terms:
5(6 + y) = y + 3 + 2y
(6 * 5 + y * 5) = y + 3 + 2y
(30 + 5y) = y + 3 + 2y

Reorder the terms:
30 + 5y = 3 + y + 2y

Combine like terms: y + 2y = 3y
30 + 5y = 3 + 3y

Solving
30 + 5y = 3 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
30 + 5y + -3y = 3 + 3y + -3y

Combine like terms: 5y + -3y = 2y
30 + 2y = 3 + 3y + -3y

Combine like terms: 3y + -3y = 0
30 + 2y = 3 + 0
30 + 2y = 3

Add '-30' to each side of the equation.
30 + -30 + 2y = 3 + -30

Combine like terms: 30 + -30 = 0
0 + 2y = 3 + -30
2y = 3 + -30

Combine like terms: 3 + -30 = -27
2y = -27

Divide each side by '2'.
y = -13.5

Simplifying
y = -13.5

See similar equations:

| -0.7777(x+3)=14 | | 1/161/2 | | (4+2k)6+3k= | | 3x^2-9600x+100p=0 | | 8x-2-5x+7=2x+4 | | 909=6c+111 | | x^2+6x=952 | | 4z-2=2z+2 | | k/2=lna | | 13x^2+78x+117=0 | | 0.6666(x+13)=22 | | -1-7x-x=-23 | | x+2x=82 | | N+32=67 | | 5k-12=k | | -1+8k=79 | | 0.6667(x+13)=22 | | 5(-7x+2)=270 | | 4+21x=2.50 | | -110+8x=30+x | | 625x^4=1000x^3 | | Z-5=-11 | | -32=6x+4x+8 | | -14=2(w-3)-4w | | 6x+10=6x+94 | | (X+3)(x+6)=189 | | x+ywhenx=3 | | 1. 6x+10=6x+94 | | (b^7)^2/7 | | 3m+6=6m-3 | | -67=-(j-(-22)) | | 4(2+7x)=204 |

Equations solver categories